I wish my teacher knew eaudiobook How one question can change everything for our kids. - Schwartz, Kyle (Tantor Media, 2017)
One day, third-grade teacher Kyle Schwartz asked her students to fill-in-the-blank in this sentence: "I wish my teacher knew _____." The results astounded her. Some answers were humorous, others were heartbreaking—all were profoundly moving and enlightening. The results opened her eyes to the need for educators to understand the unique realities their students face in order to create an open, safe, and supportive place in the classroom. When Schwartz shared her experience online, #IWishMyTeacherKnew became an immediate worldwide viral phenomenon. Schwartz's book tells the story of #IWishMyTeacherKnew, including many students' emotional and insightful responses, and ultimately provides an invaluable guide for teachers, parents, and communities.